Life cycle assessment of bioelectrochemical and integrated microbial fuel cell systems for sustainable wastewater treatment and resource recovery. (15th October 2022) - Chin, Min Yee; Phuang, Zhen Xin; Woon, Kok Sin; Hanafiah, Marlia M.; Zhang, Zhen; Liu, Xiaoming
Abstract: Bioelectrochemical system (BES) is an emerging technology that can treat wastewater via microbial activity while producing energy simultaneously. The system can couple with conventional systems to improve system performance. This study aims to compare the environmental performance of BES and the integrated microbial fuel cell (MFC) systems via a life cycle assessment methodology and identify the major environmental hotspots of the system. Fifteen treatment options are assessed with the ReCiPe 2016 characterization method using SimaPro 9.2 software. The results show double chamber air-cathode microbial electrolysis cell (MEC1) and membrane distillation integrated MFC (MD + MFC) treatment options present as the most environmental favourable among the BES and integrated MFC systems, respectively, due to the offset of the environmental loads from the avoided impacts contributed by their value-added by-product, which is hydrogen fuel for MEC1 and tap water for MD + MFC. Electricity consumption dominates the environmental loads of all the BES options for up to 90% of the global warming impact category. The environmental benefits from the electricity generation of BES are minor (i.e., MFC: 0.01–2% while microbial desalination cell: 0.01–7% of the total environmental impact in a system) to offset the environmental loads incurred by the system. Platinum-based cathode incurs 2.5–24 times higher environmental burdens than non-platinum configurations in MFC under the human carcinogenic toxicity impact category. In line with Sustainable Development Goals 6 and 13, this study provides scientific references to wastewater treatment stakeholders in selecting suitable BES and integrated MFC systems to improve water sanitation and address climate change simultaneously. Graphical abstract: Image 1 Highlights: Environmental life cycle analysis for various BES and integrated MFC is conducted. Membrane distillation integrated MFC shows the highest environmental benefit. By-products recovery from integrated system provide 31–61% environmental saving. Materials used in the system affect the environmental impact significantly. Activated carbon granules and platinum electrodes incur high environmental burdens.